How Chinese Are You? : Adopted Chinese Youth and their Families Negotiate Identity and Culture - Louie, Andrea (Book collections on Project MUSE., 2015)
Chinese adoption is often viewed as creating new possibilities for the formation of multicultural, cosmopolitan families. For white adoptive families, it is an opportunity to learn more about China and Chinese culture, as many adoptive families today try to honor what they view as their children's "birth culture." However, transnational, transracial adoption also presents challenges to families who are trying to impart in their children cultural and racial identities that they themselves do not possess, while at the same time incorporating their own racial, ethnic, and religious identities. Ma.